Examination of the Effect of a 50-Hz Electromagnetic Field at 500 μT on Parameters Related With the Cardiovascular System in Rats - Zhang, Yemao; Li, Lijuan; Liu, Xingfa; Ding, Lijian; Wu, Xiong; Wang, Jin; He, Mengying; Hou, Huiying; Ruan, Guoran; Lai, Jinsheng; Chen, Chen (Frontiers in Public Health, 2020)
Background: Whether electromagnetic field (EMF) exposure affects the function of the cardiovascular system is under debate. The present study aimed to investigate the effects of 500 μT EMF exposure on the cardiovascular system in rats. Methods: Forty-eight-week-old male Sprague-Dawley rats were randomly divided into two groups: the sham group and the exposure group. During 24-week EMF exposure (20 h per day), the blood pressure and pulse rate were recorded every 4 weeks. Before sacrifice, electrocardiography, echocardiography, and cardiac catheterization analysis were conducted to evaluate the cardiac function. Meanwhile, hematoxylin-eosin (HE) staining, Western blot, and real-time polymerase chain reaction (PCR) were performed to identify morphological and molecular changes indicative of cardiac remodeling. Results: The heart rate, blood pressure, and pulse rate were not influenced by EMF exposure compared with the control group. In addition, HE staining showed no change in the morphology and arrangement of cardiomyocytes. Further, we found that the mRNA and protein levels of cardiac hypertrophy-related genes were not affected by EMF exposure. Finally, no significant difference was observed in cardiac function between the two groups by echocardiography and cardiac catheterization detection. Conclusion: The 24-week exposure to EMF at 500 μT did not have apparent effects on the cardiovascular system in rats, at least for the variables studied.